An optical investigation of thermal runway phenomenon under thermal abuse conditions. (15th October 2021) - García, Antonio; Monsalve-Serrano, Javier; Lago Sari, Rafael; Martinez-Boggio, Santiago
Highlights: Evaluation of thermal runaway with optical techniques. Schlieren technique shows significant liquid phase during venting. Natural luminosity evidences a well stablished flame for 3 s. The thermodynamic analysis provides the safety time and heat release. Abstract: This work aims at studying the thermal runaway process caused by thermal abuse using different optical techniques. A commercial Samsung ICR 18, 650 – 26 J cylindrical battery cell is exposed to different heating ramps in a Continuous Flow Vessel (CFV) to identify critical phases of the battery thermal runaway. The open volume test bed allows to increase the temperature under controlled conditions and evacuate the released gases, enhancing the visualization of the battery venting and combustion. The venting of the electrolyte and gases is seen around 200 °C. The safety time, defined as time between venting and fire, was around 3 min, with an inverse relation with respect to the heating ramp. The use of fast cameras (schlieren, Natural Luminosity and OH*) allowed to deeply understand the phenomena of liquid electrolyte and generated internal gases venting as well as the combustion process.